Match Quality, New Information, and Marital Dissolution - Weiss, Yoram; Willis, Robert J. (Journal of Labor Economics, 1997)
"This article investigates the role of surprises in marital dissolution [in the United States]. Surprises consists of changes in the predicted earning capacity of either spouse. Data from the National Longitudinal Study of the High School Class of 1972 is used. We find that an unexpected increase in the husband's earning capacity reduces the divorce hazard, while an unexpected increase in the wife's earning capacity raises the divorce hazard. Couples sort into marriage according to characteristics that are likely to enhance the stability of the marriage. The divorce hazard is initially increasing with the duration of marriage, and the presence of children and high levels of property stabilizes the marriage."